#### Answer

-1

#### Work Step by Step

$\frac{r-13}{13-r}=\frac{r-13}{-(r-13)}=\frac{1}{-1}\times\frac{r-13}{13-r}=-1\times1=-1$

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

-1

$\frac{r-13}{13-r}=\frac{r-13}{-(r-13)}=\frac{1}{-1}\times\frac{r-13}{13-r}=-1\times1=-1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.